Less Known Wiw Edmle Fruits and Seeds of Uttara Kannada District of Karnataka - Hebbar, S. S.; Hegde, Gurumurthi; Hegde, G. R. (Indian Forester, 2010)
This paper deals with the lel!l8 known wild edible fruits and seeds of Uttara Kannada district of Karnataka. Leas known 12 wild edible fruit and seed bearing plants are documented. Eaeb plant i. given with the information about its family, voucher specimen number, local kannada names, place of occurrence. flowering and fruiting seasons, part used, method of osage, description of edible part and medicinal importance of the plant is also given, wherever available.